Engineering system for biological degradation of IWW’s contaminated with heavy metals using native Strains of Aspergillus sp. - Francisco J. Roque (2019)
An engineering system capable of degrading biologically in continous operation IWWs (industrial waste water) contaminated with heavy metals using native strains of Aspergillus sp. using a new technology was implemented efficiently incorporating plug flow reactor. The system was configured with eight fully stainless steel tubes packed with immobilized cells of Aspergillus sp. circularly arranged within a cylindrical tank way to provide heating jacket thermostating system possessing bioscrubber fungal strains to develop its maximum performance at 30 ± 1°C, likewise, was also an electric 2 HP nominal power centrifuge which was fed wastewater and recirculated through the system to get their purging heavy metals (Cu, Zn, Cd and Pb) so that when the system worked was allowed into the raw water to the tubes containing immobilized fungal cells and with which contact is executed removal and cleaning of heavy metals described above flowing water. The system used in its design included peripherals like two water tanks, one of them was found in raw wastewater and treated water the other got to operate the system and that proved to be the desired effluent, both are connected to the pump centrifuge tubes and packaged with fungal strains.